HUBUNGAN DUKUNGAN SOSIAL PASANGAN DENGAN KONFLIK PEKERJAAN-KELUARGA PADA IBU BEKERJA - Utami, Karina Putri; Wijaya, Yeny Duriana (Jurnal Psikologi, 2018)
Working mother frequently dealing with difficult emerged from family side and working side, working mother ought to faced simultaneous occurence when compliance one role that would make more difficult to compliance the other, that condition described as work-family conflict. Work-family conflict can be reduced by social support from husband as a significant other who can provide an encouragements, advices and also assistance to do some household and childcare. This research used quantitative non-experimental method with non-probability sampling technique with snowball sampling, the samples were 58 working mothers. Partner social support scales has coefficient reliability (Î±) = 0.946 consists 42 items and work-family conflict (Î±) = 0.946 consists 31 items. This research has result significant negative correlation (sig = 0.000 dan r = -0.532) between partner social support and work-family conflict. Working mother received high level of partner social support (27.6%) and perceived work-family conflict on low level (32.8%). Partner social support provides contribution amount 28.3% to reduce work-family conflict. The dominant dimension perceived by working mother is behaviour-based conflict that is sources from work (work interference family).Â Keywords: partner social support, work-family conflict, working mother